Ebola Virus Disease A Manual for EVD Management (Springer International Publishing, 2018)
This current manual gives an overview to management of Ebola Virus Disease outbreaks from a practical point of view. It gives an introduction to the topic, reviews the history and previous outbreaks of Ebola virus disease and gives insight to clinical features of the disease. The major part of the book presents ways of response including screening, isolation and personal protection equipment as well as waste management during disease outbreaks. New therapies and experimental drugs are discussed in further detail. The last part of the volume deals with all aspects of diagnostics and practical laboratory handling of Ebola virus. Dr. Marta Lado is the clinical lead of the King's Sierra Leone Partnership in country team. She brings together a group of authors aggregating both well-grounded basic knowledge on Ebola virus as well as deep experience with Ebola Virus Disease in the field.